2013
DOI: 10.1002/jsfa.6248
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of carnosic acid and rosmarinic acid in raw and cooked ground chicken patties

Abstract: This study demonstrates that the physical state (powder vs liquid) of CA or RA plays an important role in determining their antioxidant efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Meat and meat products are susceptible to lipid oxidation, because this process involves the oxidation of membrane‐abundant polyunsaturated fatty acids . In general, storage time had a significant influence on the development of lipid oxidation in the meat samples, as shown by the increase in TBARS values during storage.…”
Section: Resultsmentioning
confidence: 99%
“…Meat and meat products are susceptible to lipid oxidation, because this process involves the oxidation of membrane‐abundant polyunsaturated fatty acids . In general, storage time had a significant influence on the development of lipid oxidation in the meat samples, as shown by the increase in TBARS values during storage.…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant properties of rosemary leave extracts are due to their phenolic diterpene contents such as carnosol and carnosic acid [22]. Carnosic acid exhibits antioxidant [23], anti-inflammatory [11], and anti-carcinogenic activities [14,15]. The ability of carnosic acid to inhibit tumor cell proliferation was reported earlier.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found lower lipid oxidation rates in samples with added extracts compared with control. A significant relationship between phenolic content and antioxidant effect of carnosic acid and rosmarinic acid extract has been reported by Maheswarappa et al . and Carpenter et al .…”
Section: Resultsmentioning
confidence: 74%
“…The authors found lower lipid oxidation rates in samples with added extracts compared with control. A significant relationship between phenolic content and antioxidant effect of carnosic acid and rosmarinic acid extract has been reported by Maheswarappa et al 40 and Carpenter et al 41 reported relationship between phenolic content and antioxidative effect of bearberry extract in pork patties. Zengin and Baysal 42 reported antioxidant effect of clove and thyme essential oil in minced beef.…”
Section: Changes In Trars Of Raw Ground Pork Meat Samplesmentioning
confidence: 79%